2016
DOI: 10.1093/mnras/stw3206
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of the Magellanic Bridge Based on OGLE IV RR Lyrae Variables

Abstract: We examine the properties of the Magellanic Bridge connecting the Large and Small Magellanic Clouds using ab-type RR Lyrae variables from the extensive dataset of the Optical Gravitational Lensing Experiment (OGLE), Phase IV data release. The metallicities of the RR Lyraes are determined from the characteristics of their light curves, with an average abundance of [Fe/H] = -1.790 ± 0.011 (sem) in the Magellanic Bridge. From the individual reddenings of these stars, derived via their minimum light curve colors, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Despite later studies (Nidever et al 2011;Bagheri et al 2013;Skowron et al 2014;Noël et al 2013Noël et al , 2015Jacyszyn-Dobrzeniecka et al 2017) uncovering the presence of intermediate-age/old stellar populations in the central and western regions of the MB, the interpretations as to their origin differed. While Noël et al (2013Noël et al ( , 2015 and Carrera et al (2017) supported a tidal origin for these intermediateage stars in the MB, Jacyszyn-Dobrzeniecka et al (2017) and Wagner-Kaiser & Sarajedini (2017) suggested them as part of the overlapping stellar halos of the MCs. Belokurov et al (2017) reported the existence of a stellar tidal bridge from the study of RR Lyrae stars in the Gaia data release 1 (DR1) (Gaia Collaboration et al 2016) and found that this old stellar bridge is not aligned with the gaseous MB but is shifted by ∼ 5 • from the bridge traced by young main sequence stars (the latter is well aligned with the gaseous bridge).…”
Section: Introductionmentioning
confidence: 94%
“…Despite later studies (Nidever et al 2011;Bagheri et al 2013;Skowron et al 2014;Noël et al 2013Noël et al , 2015Jacyszyn-Dobrzeniecka et al 2017) uncovering the presence of intermediate-age/old stellar populations in the central and western regions of the MB, the interpretations as to their origin differed. While Noël et al (2013Noël et al ( , 2015 and Carrera et al (2017) supported a tidal origin for these intermediateage stars in the MB, Jacyszyn-Dobrzeniecka et al (2017) and Wagner-Kaiser & Sarajedini (2017) suggested them as part of the overlapping stellar halos of the MCs. Belokurov et al (2017) reported the existence of a stellar tidal bridge from the study of RR Lyrae stars in the Gaia data release 1 (DR1) (Gaia Collaboration et al 2016) and found that this old stellar bridge is not aligned with the gaseous MB but is shifted by ∼ 5 • from the bridge traced by young main sequence stars (the latter is well aligned with the gaseous bridge).…”
Section: Introductionmentioning
confidence: 94%
“…These radially pulsating variables are valuable tracers of old and metal-poor stellar populations and provide extragalactic distance estimates with well-defined period-luminosity relations (PLRs), especially in the near-infrared bands (Longmore et al 1986;Bono et al 2001;Catelan et al 2004;Sollima et al 2006;Muraveva et al 2015;Braga et al 2015;Neeley et al 2015). Additionally, a narrow range of the intrinsic colors of RR Lyrae stars also serves as a useful reddening indicator (Sturch 1966; Ma-E-mail:susmitadas130@gmail.com teo et al 1995;Guldenschuh et al 2005;Wagner-Kaiser & Sarajedini 2017). RR Lyrae and Cepheid variables are both excellent probes for the understanding of the theory of stellar pulsation and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Though several studies (Nidever et al 2011;Bagheri, Cioni & Napiwotzki 2013;Noël et al 2013;Skowron et al 2014;Noël et al 2015;Belokurov et al 2017;Jacyszyn-Dobrzeniecka et al 2017Massana et al 2020) found intermediate-age/old (age > 2 Gyr) stars around the MB region, the interpretations of their origin differed. While Noël et al (2013Noël et al ( , 2015 and Carrera et al (2017) supported a tidal origin for these intermediate-age stars, Jacyszyn-Dobrzeniecka et al (2017) and Wagner-Kaiser & Sarajedini (2017) suggested them as part of the overlapping stellar halos of the MCs. No conclusive evidence of a stellar counterpart (consisting of stars older than 1.5 Gyr) to the MS has been found so far.…”
Section: Introductionmentioning
confidence: 92%